2009
DOI: 10.1038/sj.bjc.6605115
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of BRCA1 germ-line mutations to breast cancer in Greece: a hospital-based study of 987 unselected breast cancer cases

Abstract: BACKGROUND: In most Western populations, 5 -10% of all breast cancer cases can be attributed to major genetic factors such as predisposing mutations in BRCA1 and BRCA2, with early-onset cases generally considered as an indicator of genetic susceptibility. Specific BRCA1 and BRCA2 mutations or different mutation frequencies have been identified in specific populations and ethnic groups. Previous studies in Greek breast and/or ovarian cancer patients with family history have shown that four specific BRCA1 mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
12

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 36 publications
2
30
0
12
Order By: Relevance
“…In our previous studies on the prevalence of BRCA1 and BRCA2 mutations in the Greek population (classified as Caucasian and genetically heterogeneous), we have found that a mutation in either gene is present in 20.5 % in a high-risk group selected for moderate to severe family history (n = 287) [31], while a BRCA1 founder mutation was present in 10 % of young (\40 years) breast cancer patients regardless of family history compared to 2.6 % of all breast cancer patients screened (n = 987) [32].…”
Section: Introductionmentioning
confidence: 92%
“…In our previous studies on the prevalence of BRCA1 and BRCA2 mutations in the Greek population (classified as Caucasian and genetically heterogeneous), we have found that a mutation in either gene is present in 20.5 % in a high-risk group selected for moderate to severe family history (n = 287) [31], while a BRCA1 founder mutation was present in 10 % of young (\40 years) breast cancer patients regardless of family history compared to 2.6 % of all breast cancer patients screened (n = 987) [32].…”
Section: Introductionmentioning
confidence: 92%
“…Hereditary breast cancer constitutes 5-10% of all breast cancer cases. Major genetic factors, such as predisposing mutations in the BRCA1 and BRCA2 genes, are generally considered an indicator of genetic susceptibility in the case of early onset [4,5]. Women with a BRCA1 (MIM# 113705) or BRCA2 (MIM# 600185) germline mutation are at high risk of developing breast and/or ovarian cancer [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Most subjects with pdac were white (79.2% maternal, 80.1% paternal), with an enrichment of cases (37.4%) having French-Canadian ancestry (at least 1 parental origin, Table iii). In addition, 56.8% of pdac-affected subjects had an ancestry (that is, French-Canadian, Ashkenazi Jewish, Greek, German, Polish, or Latvian) known to harbour recurrent germline ("founder") mutations in the BRCA1, BRCA2, and PALB2 pdac predisposing genes (Table iii) [11][12][13][14][15][16][17][18][19] . Table iii also shows data describing education, environmental exposures, weight loss, and history of type 2 diabetes and pancreatitis for enrolled patients with pdac.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, more than half the enrolled patients in the qpcs affected with pdac (56.8%) had an ancestry (at least 1 parental origin) known to harbour founder BRCA1 and BRCA2 mutations [11][12][13][14][15][16][17][18][19] . The founder populations represent a genetically enriched subgroup ideal for gene discovery studies 8,[37][38][39] .…”
Section: Discussionmentioning
confidence: 99%